PHP CodeIgniter for absolute beginners - Safari eBooks ([Place of publication not identified] : Packt Publishing, 2018)
"Learn CodeIgniter from scratch with this simple and easy to master course! Building dynamic websites is not an easy challenge and requires time and effort dedicated to coding every bit of the website, which is why anytime there is a new tool that promises to ease the woes of coding, developers always jump at the chance to try it. CodeIgniter is a simple open-source framework that makes it the coding tasks easier by providing a faster way to set up a PHP website from the ground-up. This tool with a small framework, ensures that developers can design websites that are light, fast and dynamic. So, for any developer that wants to become a server-side master, this is a tool that they should definitely have in their toolkit. But, it's not always easy to find a course that is clear and concise and targets exactly what you are looking for! This is why we have designed this course with an aim to do just that. Using a no-fluff and clear approach at the topic at hand, this tutorial will breakdown CodeIgniter into simple and easy to learn videos. At the end of this course, you will have not only learned the CodeIgniter framework, but you will actually be able to start building your own projects from scratch. In addition to knowledge, this course will also give you the practical hands-on experience and the confidence to start coding your own websites. While the theoretical will include numerous examples, at the end of the theoretical session, you will then actually practice what you learn by building a complete project from scratch with the framework."--Resource description page.
Title from resource description page (Safari, viewed March 7, 2018).
Keywords: CodeIgniter (Computer file); Application software -- Development; Internet programming; PHP (Computer program language); Electronic books